Geometric analysis of the urethral‐vaginal interface curvature in women with and without stress urinary incontinence: A pilot magnetic resonance imaging study. Issue 1 (22nd November 2021) - Hong, Christopher X.; Sheyn, David D.; Sammarco, Anne G.; DeLancey, John O.
Abstract: Aims: To evaluate differences in the curvature of the urethral‐vaginal interface in women with and without stress urinary incontinence (SUI) using geometric morphometric analysis techniques. Methods: We conducted a pilot case–control study using magnetic resonance imaging (MRI) scans of 18 women with and without SUI. The urethral‐vaginal interface at the level of the mid‐urethra was fitted with a second‐order polynomial regression. The chord length and chord‐to‐vertex length of the resulting parabolic curve were used to calculate the arc length and radius of a circular arc fitted to the interface curvature. Demographic characteristics and Pelvic Organ Prolapse Quantification (POP‐Q) parameters were collected. Subjects were stratified by those with and without SUI, as well as by those with and without anterior wall prolapse beyond 2 cm proximal to the hymen (Aa > −2 cm). Results: The radius of the urethral‐vaginal interface curvature was not found to be different between subjects with and without SUI (8.8 vs. 9.2 mm, p  = 0.53); however, this value was smaller in subjects with Aa > −2 (8.4 vs. 11.9 mm, p  = 0.03). The chord length, chord‐to‐vertex length, and arc length comprising the urethral‐vaginal interface curvature were similar between subjects with and without SUI, and between subjects with and without Aa > −2 cm ( p  > 0.05 for all). Conclusions: In this pilot study population, the radius of the urethral‐vaginal interface curvature at the mid‐urethra was smaller among women with anterior vaginal wall prolapse beyond 2 cm proximal to the hymen. A difference in the urethral‐vaginal interface curvature among women with and without SUI was not found.